The Importance of Trade Unions / Labor Unions in Companies - Ahmadi; Moh Abu Mahmud (Widya Pranata Hukum : Jurnal Kajian dan Penelitian Hukum, 2024)
An employment relationship occurs if there are elements of orders, wages, work carried out between the employer and the worker/laborer. Once there is an employment relationship, workers/laborers have the right to establish a workers/labor union within the Company. After workers/laborers have a trade union/labor union organization in the company, the worker/labor union has rights that must be accepted by the company in order to achieve dynamic work relations within the company. The rights of workers/labor unions that must be accepted after being established in a company are; represent workers/laborers to negotiate with employers, make collective work agreements, fight for share ownership for workers/laborers in the company and fight for the rights of every worker/laborer as regulated in labor legislation. Employers should not be arbitrary in providing every right to workers/laborers in the company because the rights of every worker have been regulated in legislation, for example regarding the Regency Minimum Wage (UMK) which has been regulated by the Governor's Regulation. Every company must comply with it to pay wages for its employees according to the UMK. . UMK is a safety net for workers to earn wages in order to achieve peace of mind at work. Even though wages are determined every year, if employers want to pay above the minimum wage, it is also permissible because workers/laborers are company assets that need to be looked after in order to make the production process more productive. But sometimes entrepreneurs underestimate workers/laborers because there are many workers out there who are unemployed, so between support and demand, supply and demand are not balanced, the bargaining position of workers/laborers is very low. So, to protect workers/laborers, it is absolutely necessary to have a workers/labor union in the company to act as a representative in every industrial relationship with the employer. One of the roles of trade unions is to represent workers/laborers when facing employers' lawsuits, whether regarding employment disputes or other disputes. One of the dispute claims that is submitted must be carried out by bipartite efforts first between the worker/laborer and the employer after which mediation is carried out by the department that handles employment issues.